MEASUREMENT OF THE ELECTRICAL QUANTITIES OF THE WET SCRUBBER - Ivanišević, Mladen; Zoranović, Miodrag (Journal on Processing and Energy in Agriculture, 2023)
With the aim of reducing environmental, energy and quality problems in the field of farming of animal species, laboratory for agricultural technique in animal husbandry, Department of Agricultural Engineering, Faculty of Agriculture, University of Novi Sad, integrally develops a system for wet air purification, wet scrubber and its energy control. The goal of electrical measurements in wet scrubber is to determine instantaneously and interval-accurate values ​​of electrical quantities, defined by physical methods. Devices for electrical measurements give precise values ​​of basic electrical quantities: current, electromotive force, voltage, impedance, electrical work, power and energy. Simple periodic voltages and currents are crucial for wet scrubber drive elements. Simple periodic voltages and currents are determined by three quantities: amplitude, frequency and phase. The paper presents the basic patterns for the measured values ​​of wet scrubber drive elements: AC operation, AC power, AC power with active resistances in the circuit and AC power with impedance in the electric circuit. The presence of a large number of drive elements for partial operational actions in wet scrubber is the basic reason for choosing a central atomizer, as the object of methodologically original energy analysis of this work.